Recent advances in the development of nanoparticles for multimodality imaging and therapy of cancer. Issue 3 (25th October 2019) - Liu, Mei; Anderson, Redmond‐Craig; Lan, Xiaoli; Conti, Peter S.; Chen, Kai
Abstract: This review explores recent work directed toward the development of nanoparticles (NPs) for multimodality cancer imaging and targeted cancer therapy. In the growing era of precision medicine, theranostics, or the combined use of targeted molecular probes in diagnosing and treating diseases is playing a particularly powerful role. There is a growing interest, particularly over the past few decades, in the use of NPs as theranostic tools due to their excellent performance in receptor target specificity and reduction in off‐target effects when used as therapeutic agents. This review discusses recent advances, as well as the advantages and challenges of the application of NPs in cancer imaging and therapy.